2018
DOI: 10.1017/s0007485318000135
|View full text |Cite
|
Sign up to set email alerts
|

Olive cultivar and maturation process on the oviposition preference ofBactrocera oleae(Rossi) (Diptera: Tephritidae)

Abstract: The olive fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), is a key-pest in the main olives producing areas worldwide, and displays distinct preference to different olive cultivars. The present work intended to study oviposition preference towards three Portuguese cultivars (Cobrançosa, Madural, and Verdeal Transmontana) at different maturation indexes. Multiple oviposition bioassays (multiple-choice and no-choice) were conducted to assess cultivar preference. No-choice bioassays were conducted to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…However, regardless of the reason for the egg-laying site selection, insects choose to lay eggs on well-nourished hosts or tissue to ensure the healthy development and survival of their offspring (Jeong et al, 2016;Malheiro et al, 2018;Mitchell et al, 2019). Here, we found that O. strigicollis laid the most eggs at the tip of the KBPs, which indicated this location as their preferred oviposition site.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, regardless of the reason for the egg-laying site selection, insects choose to lay eggs on well-nourished hosts or tissue to ensure the healthy development and survival of their offspring (Jeong et al, 2016;Malheiro et al, 2018;Mitchell et al, 2019). Here, we found that O. strigicollis laid the most eggs at the tip of the KBPs, which indicated this location as their preferred oviposition site.…”
Section: Discussionmentioning
confidence: 67%
“…Of the many plant morphological features, the plant physical structure is one of the important factors that is known to significantly affect this reproductive behavior, either positively (Benedict, Leigh & Hyer, 1983;Griffen & Yeargan, 2002) or negatively (Simmons & Gurr, 2004). The mechanisms that drive female oviposition decisions have evolved such that female insects will choose sites with the optimal plant-based resources for the survival of their offspring (Malheiro et al, 2018;Mitchell et al, 2019). However, whether other factors influence the choice of oviposition sites by predatory insects remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Megaritiki. Variation among different olive varieties in the emitted fruit VOCs may be related to their susceptibility to injury by the olive fly, although other factors could also be involved in the olive fly's preference such as the maturity index, weight and volume (Gonçalvez et al., 2012; Neuenschwander et al., 1985), fruit colour (Katsoyannos & Kouloussis, 2001; Malheiro, Casal, Cunha, et al., 2015; Malheiro et al., 2018; Neuenschwander et al., 1985), surface waxes (Kombargi et al., 1998) and fatty acid composition (Gonçalvez et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fruit characteristics are crucial for the oviposition site selection of B. oleae 6,29 . Moreover, the quality of oviposition sites can be deeply altered by exogenous factors, as the presence of prior infestations 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Aside from female oviposition preferences, fruit characteristics may influence the larval development 4 . Among fruit features, the ripening stage influences B. oleae oviposition choices, since females generally prefer to oviposit on unripe green olives 4,6 . To successfully locate and select oviposition sites, B. oleae adult females mainly rely on olfactory cues, namely volatile organic compounds (VOCs, hereafter) produced by the tree 20 .…”
mentioning
confidence: 99%